Ultrastructure of the membrane attack complex of complement: detection of the tetramolecular C9-polymerizing complex C5b-8. - Tschopp, J (1982)
The ultrastructure of the membrane attack complex (MAC) of complement had been described as representing a hollow cylinder of defined dimensions that is composed of the proteins C5b, C6, C7, C8, and C9. After the characteristic cylindrical structure was identified as polymerized C9 [poly(C9)], the question arose as to the ultrastructural identity and topology of the C9-polymerizing complex C5b-8. An electron microscopic analysis of isolated MAC revealed an asymmetry of individual complexes with respect to their length. Whereas the length of one boundary (+/- SEM) was always 16 +/- 1 nm, the length of the other varied between 16 and 32 nm. In contrast, poly(C9), formed spontaneously from isolated C9, had a uniform tubule length (+/- SEM) of 16 +/- 1 nm. On examination of MAC-phospholipid vesicle complexes, an elongated structure was detected that was closely associated with the poly(C9) tubule and that extended 16-18 nm beyond the torus of the tubule and 28-30 nm above the membrane surface. The width of this structure varied depending on its two-dimensional projection in the electron microscope. By using biotinyl C5b-6 in the formation of the MAC and avidin-coated colloidal gold particles for the ultrastructural analysis, this heretofore unrecognized subunit of the MAC could be identified as the tetramolecular C5b-8 complex. Identification also was achieved by using anti-C5 Fab-coated colloidal gold particles. A similar elongated structure of 25 nm length (above the surface of the membrane) was observed on single C5b-8-vesicle complexes. It is concluded that the C5b-8 complex, which catalyzes poly(C9) formation, constitutes a structure of discrete morphology that remains as such identifiable in the fully assembled MAC, in which it is closely associated with the poly(C9) tubule.